Identifying the Dynamics of Real Interest Rates and Inflation: Evidence Using Survey Data - Pennacchi, George G. (Review of Financial Studies, 1991)
[In the context of an equilibrium asset-pricing model, the dynamics of the instantaneous real interest rate and the instantaneous rate of expected inflation are estimated. Unlike previous models, we allow real interest rates and inflation to be mutually dependent processes. The model is estimated as a state-space system that includes observations on various maturity Treasury bills and NBER-ASA survey forecasts of inflation. Over the period 1968-1988, we find evidence that instantaneous real interest rates and expected inflation are significantly negatively correlated. Real interest rates also display greater volatility and weaker mean reversion than expected inflation.]